Beyond Umami: Understanding the effect of volatiles and γ-glutamyl peptides on koku sensation in matured cheese and cheese powder - Shaghayegh Keshanidokht; Pier Paolo Becchi; Husnain Raza; Michael Bom Frøst; Mikael Agerlin Petersen; Luigi Lucini; Valentin Rauh; Lene Buhelt Johansen; Ole G. Mouritsen; Amalie Søndergaard Warming; Inger Hansen; Karsten Olsen (International Dairy Journal, 2026)

Household-Level Environmental Exposure in Rural Arctic Alaska: An Integrated Assessment of Water, Soil, and Indoor Air - Valentin Romanovski; Somayeh Asadi; Parham Azimi; Zahra Keshavarz; Cody McIntyre; Donovan Johnson; Joseph G. Allen (Environmental Research, 2026)

Exertional dyspnea in older adults: the effects of mechanical unloading of the thorax - Abidan Abulimiti; Valentin Mons; Satyam Sarma; Andrew R. Tomlinson; Bryce N. Balmain; Tony G. Babb (European Journal of Applied Physiology, 2026)

Tailoring a wetting- and scaling-resistant superhydrophobic membrane for high-efficiency membrane distillation of 99TcO4−/ReO4− radioactive wastewater - Xiangjun Liao; Huining Zhang; Yuxiao Tian; Guangtai Zheng; Shijian Pan; Jing Chen; Yuri A. Ustynyuk; Valentin G. Nenajdenko; Yuan Liao; Cheng-peng Li (Desalination, 2026)

Possible role of cheese in promoting a green transition - Husnain Raza; Shaghayegh Keshanidokht; Pier Paolo Becchi; Karsten Olsen; Michael Bom Frøst; Inger Hansen; Valentin Rauh; Ole G. Mouritsen (International Journal of Gastronomy and Food Science, 2026)

Comparing statistical methods for detecting weather cues of mast seeding in European beech (Fagus sylvatica) across Europe - Valentin Journé; Emily G. Simmonds; Maciej K. Barczyk; Michał Bogdziewicz (Agricultural and Forest Meteorology, 2025)

Assessing accessibility to quiet and green areas at the city scale using an agent-based transport model - Leonardo G. Luquezi; Valentin Le Bescond; Pierre Aumond; Pascal Gastineau; Arnaud Can (Landscape and Urban Planning, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Insights into the evolution of a post-failure rock slope - R. Gerstner; C. Fey; E. Kuschel; F. Lehner; G. Valentin; K. Voit; C. Zangerl (Bulletin of Engineering Geology and the Environment, 2025)
Rock slope failure is commonly regarded as the most significant phase in the evolution of an unstable rock slope. However, many rock slopes do not fail in a single event but rather in several individual ones. Such polyphase rock slope failures impose a challenge, as their post-failure evolution is hard to predict, and the time interval between the failure events, their magnitude, and running-out distance can differ significantly for each respective event. In this study, we present a unique data-set of high-resolution remote sensing data acquired from a 170 m high, steep to overhanging post-failure rock slope over a 3.5-year survey. By applying ground-based interferometric synthetic aperture radar, unmanned aerial vehicle photogrammetry, and a 3D distance approach on terrestrial laser-scan data, we unravel the post-failure rock slope evolution on the example of the Hüttschlag study site (Salzburg, Austria). Accompanied by meteorological data and supported by a discrete element modelling approach, i.e. the asymmetric Voronoi logic, we (i) prove that the post-failure rock slope remains an active system, even 3.5 years after the latest major rock slope failure event, (ii) outline advantages and limitations of the respective remote sensing techniques, (iii) emphasise the challenge of identifying unambiguous triggers, and link this challenge to progressive failure within a fractured, anisotropic rock mass. Our findings highlight the importance of considering the time-dependency of rock mass strength and improve our understanding of post-failure rock slope evolution and rock mechanical processes in complex geological media.

Control performance of Amphibian Metamorphosis Assays with Xenopus laevis - James R. Wheeler; Raechel Puglisi; Adriana C. Bejarano; Zhenglei Gao; Laurent Lagadic; Scott Glaberman; Constance A. Mitchell; Natalie Burden; Valentin Mingo; Scott G. Lynn; Michelle R. Embry (Regulatory Toxicology and Pharmacology, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Higher tree species richness and diversity in urban areas than in forests: Implications for host availability for invasive tree pests and pathogens - Benno A. Augustinus; Meinrad Abegg; Valentin Queloz; Eckehard G. Brockerhoff (Landscape and Urban Planning, 2024)

Computer modeling of polypeptide toxins and ion channels: Achieving success through failure - Valentin M. Tabakmakher; Alexey I. Kuzmenkov; Andrei M. Gigolaev; Anton O. Chugunov; Nikolay A. Krylov; Denis S. Kudryavtsev; Igor E. Kasheverov; Victor I. Tsetlin; Roman G. Efremov; Alexander A. Vassilevski (Toxicon, 2024)

Pest control, productivity, and profitability improvement of associated crops in organic banana cropping systems in Benin, West Africa - Anicet G. Dassou; Fifanou Vodouhè; Silvère Tovignan; Gervais-Claude Assogba; Gbèlidji T. Vodouhè; Wilfrid Adjimoti; René Tokannou; Valentin Kindomihou; Léonard Afouda; Aimé H. Bokonon-Ganta; Simplice D. Vodouhè (Organic Agriculture, 2024)

Performance of the IRI-2016 and IRI-Plas 2020 considering Mg II as EUV solar proxy - Blas F. de Haro Barbas; Bruno S. Zossi; Gloria Tan Jun; Manuel Bravo; Miguel Martinez-Ledesma; Valentin Venchiarutti; Gilda Gonzalez; Franco D. Medina; Trinidad Duran; Ana G. Elias (Advances in Space Research, 2023)

Early cretaceous topographic evolution associated with the collapse of the Mongol-Okhotsk orogen in Western Transbaikalia: an integrated analysis - Anastasia V. Arzhannikova; Elena I. Demonterova; Alexander V. Sizov; Marc Jolivet; Ekaterina A. Mikheeva; Alexei V. Ivanov; Sergey G. Arzhannikov; Valentin B. Khubanov (International Geology Review, 2023)

Late Paleozoic – Cretaceous paleotectonic reconstructions of NE Asia: Insights from U–Pb dating detrital zircons from sandstones in the Algan and Ust’-Belaya terranes (NE Russia) - Artem V. Moiseev; Mariia Yu. Gushchina; Sergey D. Sokolov; Paul B. O'Sullivan; Valentin B. Khubanov; Kseniya G. Erofeeva; Alexander S. Dubenskiy (Journal of Asian Earth Sciences, 2023)

Diatom DNA metabarcoding to assess the effect of natural radioactivity in mineral springs on ASV of benthic diatom communities - Lory-Anne Baker; Aude Beauger; Sofia Kolovi; Olivier Voldoire; Elisabeth Allain; Vincent Breton; Patrick Chardon; Didier Miallier; Céline Bailly; Gilles Montavon; Agnès Bouchez; Frédéric Rimet; et al. (Science of The Total Environment, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Microfluidic synthesis of metal-organic framework crystals with surface defects for enhanced molecular loading - Irina G. Koryakina; Semyon V. Bachinin; Elena N. Gerasimova; Maria V. Timofeeva; Sergei A. Shipilovskikh; Anton S. Bukatin; Aleksandr Sakhatskii; Alexander S. Timin; Valentin A. Milichko; Mikhail V. Zyuzin (Chemical Engineering Journal, 2023)

Using blood test parameters to define biological age among older adults: association with morbidity and mortality independent of chronological age validated in two separate birth cohorts - Johanna Drewelies; Gizem Hueluer; Sandra Duezel; Valentin Max Vetter; Graham Pawelec; Elisabeth Steinhagen-Thiessen; Gert G. Wagner; Ulman Lindenberger; Christina M. Lill; Lars Bertram; Denis Gerstorf; Ilja Demuth (GeroScience, 2022)
Biomarkers defining biological age are typically laborious or expensive to assess. Instead, in the current study, we identified parameters based on standard laboratory blood tests across metabolic, cardiovascular, inflammatory, and kidney functioning that had been assessed in the Berlin Aging Study (BASE) ( n = 384) and Berlin Aging Study II (BASE-II) ( n = 1517). We calculated biological age using those 12 parameters that individually predicted mortality hazards over 26 years in BASE. In BASE, older biological age was associated with more physician-observed morbidity and higher mortality hazards, over and above the effects of chronological age, sex, and education. Similarly, in BASE-II, biological age was associated with physician-observed morbidity and subjective health, over and above the effects of chronological age, sex, and education as well as alternative biomarkers including telomere length, DNA methylation age, skin age, and subjective age but not PhenoAge. We discuss the importance of biological age as one indicator of aging.

Geographical contrasts of Y‐chromosomal haplogroups from wild and domestic goats reveal ancient migrations and recent introgressions - Isaäc J. Nijman; Benjamin D. Rosen; Philippe Bardou; Thomas Faraut; Tristan Cumer; Kevin G. Daly; Zhuqing Zheng; Yudong Cai; Hojjat Asadollahpour; Bengi Çınar Kul; Wei‐Yi Zhang; Guangxin E.; et al. (Molecular Ecology, 2022)
By their paternal transmission, Y‐chromosomal haplotypes are sensitive markers of population history and male‐mediated introgression. Previous studies identified biallelic single‐nucleotide variants in the SRY , ZFY and DDX3Y genes, which in domestic goats identified four major Y‐chromosomal haplotypes, Y1A, Y1B, Y2A and Y2B, with a marked geographical partitioning. Here, we extracted goat Y‐chromosomal variants from whole‐genome sequences of 386 domestic goats (75 breeds) and seven wild goat species, which were generated by the VarGoats goat genome project. Phylogenetic analyses indicated domestic haplogroups corresponding to Y1B, Y2A and Y2B, respectively, whereas Y1A is split into Y1AA and Y1AB. All five haplogroups were detected in 26 ancient DNA samples from southeast Europe or Asia. Haplotypes from present‐day bezoars are not shared with domestic goats and are attached to deep nodes of the trees and networks. Haplogroup distributions for 186 domestic breeds indicate ancient paternal population bottlenecks and expansions during migrations into northern Europe, eastern and southern Asia, and Africa south of the Sahara. In addition, sharing of haplogroups indicates male‐mediated introgressions, most notably an early gene flow from Asian goats into Madagascar and the crossbreeding that in the 19th century resulted in the popular Boer and Anglo‐Nubian breeds. More recent introgressions are those from European goats into the native Korean goat population and from Boer goat into Uganda, Kenya, Tanzania, Malawi and Zimbabwe. This study illustrates the power of the Y‐chromosomal variants for reconstructing the history of domestic species with a wide geographical range.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

Seismic Noise Parameters as Indicators of Reversible Modifications in Slope Stability: A Review - C. Colombero; D. Jongmans; S. Fiolleau; J. Valentin; L. Baillet; G. Bièvre (Surveys in Geophysics, 2021)
Continuous ambient seismic monitoring of potentially unstable sites is increasingly attracting the attention of researchers for precursor recognition and early warning purposes. Twelve cases of long-term continuous noise monitoring have been reported in the literature between 2012 and 2020. Only in a few cases rupture was achieved and irreversible drops in resonance frequency values or shear wave velocity extracted from noise recordings were documented. On the other hand, all monitored sites showed clear reversible fluctuations of the seismic parameters on a daily and seasonal scale due to changes in external weather conditions (air temperature and precipitation). A quantitative comparison of these reversible modifications is used to gain insight into the mechanisms driving the site seismic response. Six possible mechanisms were identified, including three temperature-driven mechanisms (temperature control on fracture opening/closing, superficial stress conditions and bulk rigidity), one precipitation-driven mechanism (water infiltration effect) and two mechanisms sensitive to both temperature and precipitation (ice formation and clay behavior). The reversible variations in seismic parameters under the meteorological constraints are synthesized and compared to the irreversible changes observed prior to failure in different geological conditions.

Environment and human subsistence in Northern France at the Late Glacial to early Holocene transition - Dorothée G. Drucker; Anne Bridault; Thierry Ducrocq; Chris Baumann; Frédérique Valentin (Archaeological and Anthropological Sciences, 2020)
The Late Glacial and early Holocene (ca. 15,000–6,000 cal BP) witnessed major changes in the environmental conditions which led to the establishment of temperate vegetation and animal species, thereby offering new subsistence opportunities to the population of hunter-gatherers. Measurements of the relative abundances in 13 C and 15 N were applied to large herbivores from northern France to document the change in their habitat. During the early Holocene, red deer show a decrease in δ 13 C values most likely reflecting the effect of a dense canopy and an increase in δ 15 N values probably linked to the increased soil activity of soils in foraged territories. Aurochs and roe deer δ 13 C values also revealed a more densely forested habitat at the end of the Preboreal, while the δ 13 C values of the wild boar indicate dependence on fruits and underground tubers that were not affected by the canopy effect. Three human individuals from Val-de-Reuil and La Chaussée-Tirancourt dated to the Preboreal period provided relatively high δ 15 N values when compared with the local fauna and other early Mesolithic humans, which might have resulted from the consumption of freshwater resources especially at Val-de-Reuil. The δ 34 S values appear to depend more on the geographical location of the individual, as demonstrated by the difference among wild boar δ 34 S values between sites, rather than related to the protein source of the diet, namely, terrestrial versus aquatic. Our results confirm the influence of the forest ecosystem on the environment and diet of the considered early Mesolithic human of northern France, while the possible contribution of the aquatic ecosystem still needs to be documented.

Time and space-resolved quantification of plasma membrane sialylation for measurements of cell function and neurotoxicity - Petra Kranaster; Christiaan Karreman; Jeremias E. G. A. Dold; Alice Krebs; Melina Funke; Anna-Katharina Holzer; Stefanie Klima; Johanna Nyffeler; Stefan Helfrich; Valentin Wittmann; Marcel Leist (Archives of Toxicology, 2020)
While there are many methods to quantify the synthesis, localization, and pool sizes of proteins and DNA during physiological responses and toxicological stress, only few approaches allow following the fate of carbohydrates. One of them is metabolic glycoengineering (MGE), which makes use of chemically modified sugars (CMS) that enter the cellular biosynthesis pathways leading to glycoproteins and glycolipids. The CMS can subsequently be coupled (via bio-orthogonal chemical reactions) to tags that are quantifiable by microscopic imaging. We asked here, whether MGE can be used in a quantitative and time-resolved way to study neuronal glycoprotein synthesis and its impairment. We focused on the detection of sialic acid (Sia), by feeding human neurons the biosynthetic precursor N -acetyl-mannosamine, modified by an azide tag. Using this system, we identified non-toxic conditions that allowed live cell labeling with high spatial and temporal resolution, as well as the quantification of cell surface Sia. Using combinations of immunostaining, chromatography, and western blotting, we quantified the percentage of cellular label incorporation and effects on glycoproteins such as polysialylated neural cell adhesion molecule. A specific imaging algorithm was used to quantify Sia incorporation into neuronal projections, as potential measure of complex cell function in toxicological studies. When various toxicants were studied, we identified a subgroup (mitochondrial respiration inhibitors) that affected neurite glycan levels several hours before any other viability parameter was affected. The MGE-based neurotoxicity assay, thus allowed the identification of subtle impairments of neurochemical function with very high sensitivity.

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Temporal Variability of Dark Carbon Fixation and Bacterial Production and Their Relation with Environmental Factors in a Tropical Estuarine System - Camila N. Signori; Jean L. Valentin; Ricardo C. G. Pollery; Alex Enrich-Prast (Estuaries and Coasts, 2018)

Evolution of Brain Active Gene Promoters in Human Lineage Towards the Increased Plasticity of Gene Regulation - Konstantin V. Gunbin; Mikhail P. Ponomarenko; Valentin V. Suslov; Fedor Gusev; Gennady G. Fedonin; Evgeny I. Rogaev (Molecular Neurobiology, 2018)

Aquatic resources in human diet in the Late Mesolithic in Northern France and Luxembourg: insights from carbon, nitrogen and sulphur isotope ratios - Dorothée G. Drucker; Frédérique Valentin; Corinne Thevenet; Daniel Mordant; Richard Cottiaux; Dominique Delsate; Wim Van Neer (Archaeological and Anthropological Sciences, 2018)

Single-crystal Fe-bearing sphalerite: synthesis, lattice parameter, thermal expansion coefficient and microhardness - Dmitriy A. Chareev; Valentin O. Osadchii; Andrey A. Shiryaev; Alexey N. Nekrasov; Anatolii V. Koshelev; Evgeniy G. Osadchii (Physics and Chemistry of Minerals, 2017)

A taxonomic account of non-geniculate coralline algae (Corallinophycidae, Rhodophyta) from shallow reefs of the Abrolhos Bank, Brazil - Michel B. Jesionek; Ricardo G. Bahia; Jazmín J. Hernández-Kantún; Walter H. Adey; Yocie Yoneshigue-Valentin; Leila L. Longo; Gilberto M. Amado-Filho (Algae, 2016)

Numerical study of tides in Ontario Lacus, a hydrocarbon lake on the surface of the Saturnian moon Titan - David Vincent; Özgur Karatekin; Valentin Vallaeys; Alexander G. Hayes; Marco Mastrogiuseppe; Claudia Notarnicola; Véronique Dehant; Eric Deleersnijder (Ocean Dynamics, 2016)

Using an optical settling column to assess suspension characteristics within the free, flocculation, and hindered settling regimes - Valentin Wendling; Nicolas Gratiot; Cédric Legout; Ian G. Droppo; Catherine Coulaud; Bernard Mercier (Journal of Soils and Sediments, 2015)

Physicochemical Characterization and In Vitro Cytotoxic Effect of 3-Hydroxyflavone in a Silver Nanoparticles Complex - Mariana Voicescu; Oana Craciunescu; Lucia Moldovan; Mihai Anastasescu; Daniel G. Angelescu; Valentin S. Teodorescu (Journal of Fluorescence, 2015)

Pre-existing astrocytes form functional perisynaptic processes on neurons generated in the adult hippocampus - Marine Krzisch; Silvio G. Temprana; Lucas A. Mongiat; Jan Armida; Valentin Schmutz; Mari A. Virtanen; Jacqueline Kocher-Braissant; Rudolf Kraftsik; Laszlo Vutskits; Karl-Klaus Conzelmann; Matteo Bergami; Fred H. Gage; et al. (Brain Structure and Function, 2015)

Developing an understanding of dissolved organic matter dynamics in the giant Lake Baikal by ultrahigh resolution mass spectrometry - Yuko Sugiyama; Patrick G. Hatcher; Rachel L. Sleighter; Tomoyo Suzuki; Chizuru Wada; Tetsu Kumagai; Osamu Mitamura; Toshiya Katano; Shin-ichi Nakano; Yuji Tanaka; Valentin V. Drucker; Vladimir A. Fialkov; et al. (Limnology, 2014)

Remote sensing in microwave and gamma ranges for the monitoring of soil water content of the root zone - Leonid Vulfson; Arthur Genis; Dan G. Blumberg; Alexey Kotlyar; Valentin Freilikher; Jiftah Ben-Asher (International Journal of Remote Sensing, 2013)

Effects of differently polarized microwave radiation on the microscopic structure of the nuclei in human fibroblasts - Yuriy G. Shckorbatov; Vladimir N. Pasiuga; Elena I. Goncharuk; Tatiana Ph. Petrenko; Valentin A. Grabina; Nicolay N. Kolchigin; Dmitry D. Ivanchenko; Victor N. Bykov; Oleksandr M. Dumin (Journal of Zhejiang University-SCIENCE B, 2010)

Intussusceptive angiogenesis and its role in vascular morphogenesis, patterning, and remodeling - Andrew N. Makanya; Ruslan Hlushchuk; Valentin G. Djonov (Angiogenesis, 2009)

Antimicrobial and antileishmanial xanthones from the stem bark of Allanblackia gabonensis (Guttiferae) - A. G. B. Azebaze; B. M. W. Ouahouo; J. C. Vardamides; A. Valentin; V. Kuete; L. Acebey; V. P. Beng; A. E. Nkengfack; M. Meyer (Natural Product Research, 2008)

ZMM proteins during meiosis: Crossover artists at work - Audrey Lynn; Rachel Soucek; G. Valentin Börner (Chromosome Research, 2007)

Mitogenetic structure of brown bears ( Ursus arctos L.) in northeastern Europe and a new time frame for the formation of European brown bear lineages - URMAS SAARMA; SIMON Y. W. HO; OLIVER G. PYBUS; MARJU KALJUSTE; IGOR L. TUMANOV; ILPO. KOJOLA; ALEX A. VOROBIEV; NIKOLAI I. MARKOV; ALEXANDER P. SAVELJEV; HARRI VALDMANN; ELENA A. LYAPUNOVA; ALEXEI V. ABRAMOV; et al. (Molecular Ecology, 2007)
We estimated the phylogenetic relationships of brown bear maternal haplotypes from countries of northeastern Europe (Estonia, Finland and European Russia), using sequences of mitochondrial DNA (mtDNA) control region of 231 bears. Twenty‐five mtDNA haplotypes were identified. The brown bear population in northeastern Europe can be divided into three haplogroups: one with bears from all three countries, one with bears from Finland and Russia, and the third composed almost exclusively of bears from European Russia. Four haplotypes from Finland and European Russia matched exactly with haplotypes from Slovakia, suggesting the significance of the current territory of Slovakia in ancient demographic processes of brown bears. Based on the results of this study and those from the recent literature, we hypothesize that the West Carpathian Mountains have served either as one of the northernmost refuge areas or as an important movement corridor for brown bears of the Eastern lineage towards northern Europe during or after the last ice age. Bayesian analyses were performed to investigate the temporal framework of brown bear lineages in Europe. The molecular clock was calibrated using Beringian brown bear sequences derived from radiocarbon‐dated ancient samples, and the estimated mutation rate was 29.8% (13.3%−47.6%) per million years. The whole European population and Western and Eastern lineages formed about 175 000, 70 000 and 25 000 years before present, respectively. Our approach to estimating the time frame of brown bear evolution demonstrates the importance of using an appropriate mutation rate, and this has implications for other studies of Pleistocene populations.

5 α -Ergost-24(28)-ene-3,6-dione – new steroid from the Pacific sponge Geodinella robusta - Larisa K. Shubina; Tatyana N. Makarieva; Vladimir A. Denisenko; Andrey S. Dmitrenok; Alla G. Guzii; Pavel S. Dmitrenok; Valentin A. Stonik (Natural Product Research, 2006)

Fish diversity and its relationships with environmental variables in a West African basin - Essetchi P. Kouamélan; Guy G. Teugels; Valentin N'Douba; Gouli Gooré Bi; Tidiani Koné (Hydrobiologia, 2003)

New records of Amphipoda Hyperiidea in associations with gelatinous zooplankton - Marilene C. G. de Lima; Jean L. Valentin (Hydrobiologia, 2001)

A sensitive mapping strategy for monitoring the reproducibility of glycan processing in an HIV vaccine, RGP-160, expressed in a mammalian cell line - N.T. Tran; M. Taverna; A.H. Merry; M. Chevalier; G. Morgant; C. Valentin; D. Ferrier (Glycoconjugate Journal, 2000)

Osmoadaptation in halophilic and alkaliphilic methanotrophs - Valentina N. Khmelenina; Marina G. Kalyuzhnaya; Valentin G. Sakharovsky; Natalia E. Suzina; Yuri A. Trotsenko; G. Gottschalk (Archives of Microbiology, 1999)

Electrogenic cyclic redox chain in bacterial photosynthesis: Two regimes of operation in intact cells of Rhodospirillum rubrum - Valentin G. Remennikov; Vitaly D. Samuilov (Archives of Microbiology, 1980)

Photooxidase activity of isolated chromatophores and intact cells of phototrophic bacteria - Valentin G. Remennikov; Vitaly D. Samuilov (Archives of Microbiology, 1979)